A mixed coating diaphragm with uniformly distributed coating polymer, a preparation method thereof, and a secondary battery

By uniformly distributed fluorine -free polymer particles in the mixed coating membrane, the problem of inconsistent adhesion for coating is solved, and the high consistency bonding and good breathability of the coating are achieved. Question.

CN119092945BActive Publication Date: 2025-01-24SINOMA LITHIUM BATTERY SEPARATOR (NANJING) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411580783.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-24
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The bonding properties of fluorine-free polymers and inorganic particles are very different at different locations, resulting in poor interfacial consistency of the battery cell, high internal resistance and circulating diving.

Method used

By uniformly distributed fluorine -free polymer particles in the mixed coating membrane, it is basically the same in bonding everywhere, and the distribution of polymer particles is adjusted through specific preparation methods to ensure the uniformity of fluoride polymer particles in the coating. Sexual and suitable distribution distance.

Benefits of technology

The high consistency adhesion of the coating, good breathability, is not easy to fall off the powder, and the heat shrinkage performance is excellent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119092945B_ABST
    Figure CN119092945B_ABST
Patent Text Reader

Abstract

The present invention discloses a mixed coating diaphragm with uniformly distributed coating polymers, a preparation method thereof, and a secondary battery, and relates to the technical field of battery diaphragms. The present invention provides a mixed coating diaphragm with uniformly distributed coating polymers, so that the adhesion of the coating is basically consistent everywhere, the coating has good air permeability, is not easy to fall off and powder, and has good heat shrinkage performance. The present invention also provides a method for preparing the above-mentioned diaphragm, by regulating and controlling the polymer emulsion raw materials, the preparation of the coating slurry, the drying process after coating, etc., so that the distribution uniformity between the polymer particles is good and the distance is appropriate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery separators, and in particular to a mixed-coating separator with uniformly distributed coating polymers, a preparation method thereof, and a secondary battery. Background Art

[0002] With the development of fluorine-free polymer application technology in coatings, it is becoming more and more common to use fluorine-free polymers to replace PVDF as the material for bonding separators and positive and negative electrodes. In particular, the technical route of mixed coating of ceramics and fluorine-free polymers is not only low-cost but also has both adhesion and heat resistance. It is a very promising coating technology.

[0003] The invention patent with publication number CN 106784531A discloses a mixed coating diaphragm, in which a water-based coating formed by mixing PMMA and its copolymer and boehmite is coated on the surface of the base film to form a water-based coating. The carbonyl group in PMMA and its copolymer enhances the affinity of the diaphragm to the electrolyte. Compared with the diaphragm added with PVDF and its copolymer, the diaphragm with PMMA and its copolymer has a higher liquid absorption rate, thereby improving the conductivity of the lithium battery; the invention patent with publication number CN111987276A discloses that the addition of PMMA provides a higher bonding force for the battery diaphragm and the pole piece, thereby improving the strength of the battery cell. The addition of PMMA makes the bonding force between the composite lithium-ion battery diaphragm and the battery pole piece stronger, thereby improving the interface and further improving the cycle performance of the lithium-ion battery; the invention patent with publication number CN The invention patent 115483500A discloses that the aluminum oxide and PMMA on the surface of the diaphragm work together to improve the ionic conductivity of the diaphragm, and the spatial stability and flatness of the diaphragm are also improved, and the thermal shrinkage rate is smaller. PMMA is embedded between the aluminum oxide coatings, which increases the adhesion of the diaphragm coating and reduces the coating thickness. It can be seen that the fluorine-free polymer mixed coating diaphragm has many advantages, and the performance needs to be further improved. Summary of the invention

[0004] Improving the bonding performance of the mixed coating of inorganic particles and fluorine-free polymer particles has always been a problem to be improved. The present invention found that the bonding force provided by the same diaphragm coating at different positions is quite different, that is, the consistency of the bonding force of the coating to the electrode sheet is poor, which will affect the interface consistency of the battery cell and ultimately lead to problems such as high internal resistance and cycle drop.

[0005] In view of the above problems, the present invention provides a mixed coating diaphragm with uniformly distributed coating polymer, so that the adhesion of the coating is basically consistent everywhere, the coating has good air permeability, is not easy to fall off and powder, and has good heat shrinkage performance.

[0006] The present invention also provides a preparation method of the mixed coating diaphragm, which makes the distribution uniformity of polymer particles good and the distance between them appropriate by regulating the polymer emulsion raw materials, coating slurry preparation, and drying process after coating.

[0007] The present invention also provides a secondary battery, comprising the above-mentioned diaphragm, or the diaphragm prepared by the above-mentioned preparation method.

[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical scheme is adopted:

[0009] The first aspect of the present invention provides a mixed coating separator with uniformly distributed coating polymers, comprising: a base film and a mixed coating covering one or both sides of the base film, wherein the base film comprises a polyolefin microporous film with polyolefin as a main component, the mixed coating comprises fluorine-free polymer particles and inorganic particles, the inorganic particles are continuously distributed in the mixed coating, and the fluorine-free polymer particles are discretely distributed in the inorganic particles;

[0010] The mixed coating has the following characteristics within the field of view of area S0 under a 1K electron microscope:

[0011] (1) Within the field of view of area S0, the number N0 of fluorine-free polymer particles is 7-1000, preferably 7-500;

[0012] (2) In a field of view of area S0, the geometric center point C of a fluorine-free polymer particle in the field of view is used as the geometric center of a regular hexagon, and the field of view is divided into regular hexagonal network structures, and the area of ​​each regular hexagon of the regular hexagonal network is S2=S0 / N0; taking point C as the base point, the distances between the geometric centers of the six fluorine-free polymer particles closest to point C are measured respectively, and recorded as P1-P6;

[0013] Satisfies the following relationship:

[0014] The dispersion coefficient α is less than 1.5, and

[0015] Uniformity coefficient β<1.5;

[0016] Where, α= , , ;

[0017] P max is the maximum value of P1-P6, P min is the minimum value of P1-P6,

[0018] P x = ,

[0019] P n =1 / 2 P av ,

[0020] P av = ,

[0021] and P n ≤ P ≤ P x .

[0022] The following is a detailed description:

[0023] Basement membrane:

[0024] There is no particular restriction on the type of the base film, which can be selected according to actual needs; the base film can be a coated or uncoated base film; preferably, the base film can be selected from one or more of polyethylene film, polypropylene film, polyethylene / polypropylene composite film, polyimide film, polyvinylidene fluoride film, polyvinylidene fluoride-hexafluoropropylene film, polyamide film, and polyethylene terephthalate film.

[0025] The thickness of the base film may be 4-20 μm, preferably 5-12 μm.

[0026] The porosity of the base film may be 25-50%, preferably 30-50%.

[0027] The air permeability of the base film may be 40-200 sec / 100 cc, preferably 90-150 sec / 100 cc.

[0028] Mixed coating:

[0029] The fluorine-free polymer particles are one or more selected from polymethyl methacrylate (PMMA), thermoplastic polyurethane elastomer rubber (TPU), polyethylene terephthalate (PET), preferably polymethyl methacrylate (PMMA), and are spherical.

[0030] The average particle size (D50) of the fluorine-free polymer particles is preferably 0.5-10 μm.

[0031] The inorganic particles are one or more selected from α-alumina, γ-alumina, boehmite, calcium carbonate, barium sulfate, barium titanate, hydrotalcite, montmorillonite, spinel, titanium dioxide, silicon dioxide, zirconium dioxide, magnesium oxide, calcium oxide, beryllium oxide, magnesium hydroxide, calcium hydroxide, and silicon carbide;

[0032] The average particle size (D50) of the inorganic particles is preferably 0.05-1.5 μm.

[0033] Preferably, the mass ratio of the fluorine-free polymer particles to the inorganic particles is 0.5-35:15-35.

[0034] Preferably, the mixed coating further includes a binder, and the binder is one or more selected from polyacrylic acid, polyacrylate, and polyurethane.

[0035] Preferably, the mixed coating has a thickness of 0.5-5 μm.

[0036] Observe the mixed coating membrane under a 1K (magnification) electron microscope. Figure 1 The field of view shown in the figure has a rectangular field of view area S0 (the length of the field of view plane is a, the width is b, S0 = a × b), and S0 can be between 5000-20000 μm 2 ;

[0037] In this field of view, the number N0 of fluorine-free polymer particles is 7-1000, preferably 7-500, for example 10-150;

[0038] Randomly select a fluorine-free polymer particle in the field of view (preferably the center area of ​​the field of view, but not limited to this, try to ensure that there are other fluorine-free polymer particles distributed around the selected fluorine-free polymer particle), and place its geometric center point C on the geometric center of one of the regular hexagons. That is, first determine a fluorine-free polymer particle, and use the geometric center point C of this particle as the geometric center of the regular hexagon to draw a regular hexagon with an area of ​​S2=S0 / N0, and divide the field of view according to the size of the regular hexagon to form a regular hexagonal grid structure (N0 regular hexagons, each regular hexagon has an area of ​​S2=S0 / N0);

[0039] The distances between the base point C and the fluorine-free polymer particles in the six regular hexagons adjacent to the regular hexagon where it is located (the six nearest fluorine-free polymer particles) are measured respectively, and are recorded as P1-P6 (i.e., P1, P2, P3, P4, P5, P6), where the maximum value of P1-P6 is recorded as P max , the minimum value of P1-P6 is recorded as P min , according to P max and P min Calculate P: P = (P max +P min ) / 2;

[0040] The following conditions must be met:

[0041] Coefficient of dispersion α = <1.5, and

[0042] Uniformity coefficient <1.5;

[0043] The dispersion coefficient is less than 1.5. The smaller the dispersion coefficient, the closer the discrete distribution morphology of the fluorine-free polymer particles is to the ideal discrete state distribution in the regular hexagonal grid (the ideal discrete state distribution diagram is shown in Figure 2 As shown, the fluorine-free polymer particles are distributed in a geometric center); the uniformity coefficient is less than 1.5. The smaller the uniformity coefficient, the closer the mean value of the distance between the fluorine-free polymer particles is to the ideal distribution mean (i.e., P av ).

[0044] P x = ,

[0045] P n =1 / 2 P av ,

[0046] P av = ,

[0047] P n ≤ P ≤ P x .

[0048] When P>P x When P<P n This indicates that the local fluorine-free polymer particles are too concentrated, and the polymer particles are prone to stacking, causing the polymer particles to fall off and powder to fall off, and the coating thickness to be uneven, which in turn leads to an increase in internal resistance.

[0049] P n , P x , P av is the theoretical calculated value under the ideal state distribution, such as Figure 3 As shown, P n It represents the shortest distance from the geometric center of a regular hexagon to the border (side length) of its adjacent regular hexagon; P x It represents the longest distance from the geometric center of a regular hexagon to the border (side length) of its adjacent regular hexagon; P av Represents the distance between the geometric centers of two adjacent regular hexagons.

[0050] It should be noted that the geometric center is the most central position of an object, such as the center of a circle, the center of a sphere, the intersection of two diagonals of a parallelogram, etc. The geometric center of the fluorine-free polymer particle under the electron microscope is the center of the circle of the projection of its spherical particle, and the geometric center of a regular hexagon is the intersection of its diagonals.

[0051] In an embodiment of the present invention, the bonding strength of the mixed-coated diaphragm is >0.8N / m, preferably 2.4-5 N / m, for example, the bonding strength is 2.5 N / m, 3 N / m...4 N / m, 4.2 N / m, 4.5 N / m, 4.6 N / m, 4.8 N / m, 5 N / m,...; the range of the bonding strength of the mixed-coated diaphragm is <0.5N / m, for example, the range is 0.05 N / m, 0.1 N / m, 0.2 N / m,...

[0052] The distribution distance between the fluorine-free polymer particles is appropriate and the distribution dispersion is uniform, which not only ensures good coating adhesion but also high adhesion consistency. When the dispersion coefficient and uniformity coefficient of the present invention are exceeded, the extreme difference will be large, the local adhesion will be low, or the local fluorine-free polymer will have too much internal resistance and increase.

[0053] In an embodiment of the present invention, the permeability increase per unit coating thickness of the mixed coating membrane with uniform distribution of coating polymer is <50sec / 100cc / μm, preferably 5-30sec / 100cc / μm, for example, 5 sec / 100cc / μm, 10 sec / 100cc / μm, 15sec / 100cc / μm, 20 sec / 100cc / μm, 25 sec / 100cc / μm...

[0054] Permeability increment per unit coating thickness = (permeability of mixed coating membrane - permeability of base film) / coating thickness;

[0055] The "coating thickness" here refers to the thickness of the inorganic particle interface from the base film surface in the mixed coating. Figure 4 As shown, if the coating is located on both sides of the base film, the coating thickness h0 = (c1-b1) / 2, c1 is the total thickness of the base film 1 and the two-sided ceramic layers 2, and b1 is the thickness of the base film 1; if the coating is located on a single side of the base film, the coating thickness h0 is the difference between the thickness of the battery separator and the thickness of the base film.

[0056] Use a foam with a certain resilience and density (the present invention uses a beauty egg made of polyurethane foam), place the membrane on a horizontal table, fix the membrane with one hand, and use the foam to wipe the membrane surface from left to right 6-8 times with the other hand to remove the fluorine-free polymer particles from the coating without damaging the inorganic particle layer, thereby obtaining the thickness of the inorganic particle interface from the base membrane surface. The membrane cross section can also be observed under an electron microscope for measurement.

[0057] The more uniformly the fluorine-free polymer particles are distributed locally, the better the air permeability of the coating; if the fluorine-free polymer particles are distributed too densely locally, the air permeability of the local area will decrease.

[0058] In the embodiment of the present invention, the heat shrinkage rates of the mixed-coated separator with uniformly distributed coating polymers after being kept at 130° C. for 1 hour in the machine direction MD and the transverse direction TD are both less than 5%.

[0059] The more uniform the distribution of the fluorine-free polymer particles is, the more uniform the distribution of the inorganic particles is. When there are too many fluorine-free polymer particles in a certain area, the distribution uniformity of the inorganic particles in that area will be unsatisfactory, resulting in poor thermal shrinkage performance.

[0060] In the embodiment of the present invention, the powder loss rate of the mixed coating diaphragm with uniformly distributed coating polymer is less than 5%.

[0061] The local dispersion of fluorine-free polymer particles is too concentrated, and the polymer particles are prone to stacking, causing problems such as polymer particles falling off and powdering, which in turn leads to an increase in internal resistance.

[0062] In the embodiment of the present invention, the coverage rate of the fluorine-free polymer particles on the mixed coating layer in the mixed coating membrane with uniform distribution of the coating polymer (the area ratio of the fluorine-free polymer particles in the coating layer) is less than 39%.

[0063] The coverage rate must be less than 39%. Otherwise, the number of fluorine-free polymer particles is too small and the bonding force is low. If the number of fluorine-free polymer particles is too large, stacking will occur, resulting in abnormal diaphragm thickness and easy falling off.

[0064] A second aspect of the present invention provides a method for preparing a mixed-coating diaphragm with uniformly distributed coating polymers, comprising the following steps:

[0065] S1. Homogenize the fluorine-free polymer emulsion using a 360° flip rocker; the solid content of the fluorine-free polymer emulsion is 8-45%; the homogenization time is 20-60 minutes;

[0066] S2, dispersing the inorganic particles and the dispersant emulsion in water to obtain a dispersion; the dispersion time is 20-40 minutes;

[0067] S3, adding the homogenized fluorine-free polymer emulsion, binder A emulsion, binder B emulsion and wetting agent to the dispersion liquid, stirring and dispersing to obtain a mixed slurry; the stirring and dispersing temperature is 5-40°C, the stirring and dispersing speed is 100-1000rpm, and the stirring and dispersing time is 20-60min; the viscosity of the mixed slurry is 30-300mPa·S, and the solid content of the mixed slurry is 20-40%;

[0068] S4. After the slurry is prepared into a finished product, it is continuously stored at 20-150 rpm until it is applied to the coating machine;

[0069] S5. Apply the finished slurry on the base film, first dry it at 50-70°C, then dry it at 70-90°C, and coat it at a speed of 100-200 m / min to obtain a mixed-coated separator.

[0070] S1:

[0071] The solid content of the fluorine-free polymer emulsion raw material should be designed to be between 8-45%, preferably 10%-30%. If the solid content is too high, the fluorine-free polymer will easily settle and harden, while if the solid content is too low, the distribution uniformity of the fluorine-free polymer in the slurry will be reduced.

[0072] Before adding the fluorine-free polymer emulsion, it needs to be shaken by a homogenizing device before feeding to avoid uneven distribution of the fluorine-free polymer particles. The present invention uses a 360° flip rocker for homogenization. The homogenization time is 20-60 minutes. If the homogenization time is too short, the distribution of the fluorine-free polymer will be uneven. The remaining material and tail barrel (the remaining material after one feeding, which is also the first barrel for the next feeding) in actual production will affect the actual amount of fluorine-free polymer added, resulting in a decrease in the amount of fluorine-free polymer in the raw material; if the homogenization time is too long, it will lead to an increase in bubbles, that is, the risk of deformation of the fluorine-free polymer spheres, and deformation will easily cause particle agglomeration.

[0073] S2:

[0074] The dispersion time of inorganic particles is 20-40 minutes. If the dispersion time is too short, the interlocking effect of inorganic ceramics and fluorine-free polymers in the coating will be worse. The smaller the uniformity coefficient, the lower the peeling force and the higher the powder loss rate.

[0075] S3:

[0076] After the fluorine-free polymer is added to the slurry and mixed, the dispersion should be carried out at 5-40℃. If the temperature is too low, the wettability of the fluorine-free polymer will be reduced, resulting in aggregation and missing coating. If the temperature is too high, the fluorine-free polymer will be close to Tg, resulting in deformation or melting of the fluorine-free polymer. Deformation or melting can easily cause particle agglomeration. The fluorine-free polymer is added to the solution after the ceramic is dispersed, and dispersed between 20-1000rpm (for example, the speed of the dispersion disk is 300-1000rpm, and the speed of the anchor stirring paddle is 20-300rpm). The dispersion time should be ≥20min. If the dispersion speed is too low, the fluorine-free polymer is unevenly distributed in the slurry, resulting in uneven fluorine-free polymer during coating; if the speed is too high, foam will be generated, causing the polymer particles to deform and easily causing particle agglomeration. The viscosity of the obtained slurry should be between 30-300mPa·S, and the solid content of the slurry should be between 20-40%, preferably 25-35%. Too high solid content will increase the air permeability value-added, while too low solid content will give PMMA more space to move freely in the solution, and the degree of freedom will increase, resulting in reduced initial dispersibility.

[0077] S4:

[0078] After the slurry is prepared into a finished product, it needs to be stored continuously at 20-150 rpm, preferably 50-100 rpm until it is applied to the coating machine.

[0079] S5:

[0080] The coating method may be a gravure roller, a wire rod, spraying, dipping, etc., and the present invention preferably uses an anilox gravure roller.

[0081] The drying method is to evaporate the solvent first and then solidify it, that is, the temperature is low (50-70℃) first and then high (70-90℃), to avoid the violent discharge of local water vapor during the solvent volatilization process, which causes the fluorine-free polymer to perform violent Brownian motion. Therefore, this process slows down the kinetic energy of the balls and makes the distribution of the fluorine-free polymer in the coating more uniform.

[0082] In the embodiment of the present invention, the dispersant can be selected from one or more of sodium polyacrylate, triethylhexyl phosphoric acid, sodium lauryl sulfate, methyl amyl alcohol, polyacrylamide, guar gum, and fatty acid polyethylene glycol ester. The solid content of the dispersant emulsion is 40-60%, preferably 50%.

[0083] In the embodiment of the present invention, the binder A is a water-soluble binder, which can be selected from one or more of acrylic acid, acrylic acid polymer, and polyacrylonitrile. The solid content of the binder A emulsion is 10-45%, preferably 20%.

[0084] In the embodiment of the present invention, the binder B is an emulsion binder, which can be selected from one or more of polyacrylate, polymethyl cellulose, SBR, and polyvinyl alcohol. The solid content of the binder B emulsion is 20-50%, preferably 40%.

[0085] In the embodiment of the present invention, the wetting agent can be selected from one or more of polyoxyethylene alkylphenol ether, polyoxyethylene fatty alcohol ether, polyoxyethylene polyoxypropylene block copolymer, and the purity of the wetting agent is above 99%.

[0086] In the embodiment of the present invention, the mixed coating slurry includes the following components by weight: 0.5-35 parts of fluorine-free polymer emulsion, 15-35 parts of inorganic particles, 0.2-1 parts of dispersant emulsion, 0.5-5 parts of binder A emulsion, 0.5-5 parts of binder B emulsion, 0.001-0.1 parts of wetting agent and 40-60 parts of water.

[0087] According to the method provided in the second aspect of the present invention, a mixed coating separator according to any embodiment of the first aspect of the present invention can be obtained. Meanwhile, the mixed coating separator according to any embodiment of the first aspect of the present invention is not limited to being prepared by the method provided in the present invention.

[0088] The third aspect of the present invention provides a secondary battery, comprising a mixed coating separator with uniform distribution of coating polymer provided by the first aspect of the embodiment of the present invention or a mixed coating separator with uniform distribution of coating polymer prepared by the preparation method provided by the second aspect of the embodiment of the present invention.

[0089] The battery separator provided in the embodiment of the present invention can be used in different types of batteries, so there is no particular restriction on the type of battery, and it can be selected according to actual needs. Preferably, it can be used in secondary batteries, especially secondary batteries containing liquid electrolytes, such as lithium ion batteries, sodium ion batteries, etc.

[0090] Beneficial effects:

[0091] The dispersion coefficient and uniformity coefficient of the fluorine-free polymer particles in the mixed coating diaphragm provided by the present invention meet the requirements, the distribution distance between the fluorine-free polymer particles is appropriate, and the distribution dispersion is uniform, so that the adhesion of the coating at various locations remains basically consistent, and the coating has good air permeability, is not easy to fall off and powder, and has good heat shrinkage performance.

[0092] A preparation method of a mixed coating diaphragm provided by the present invention achieves good distribution uniformity and appropriate distance between polymer particles by regulating and controlling polymer emulsion raw materials, coating slurry preparation, drying process after coating, and the like.

[0093] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS

[0094] Figure 1 This is the SEM image of the mixed coating membrane under a 1K electron microscope;

[0095] Figure 2 This is the distribution diagram of fluorine-free polymer particles under ideal conditions;

[0096] Figure 3 P n , P x , P av Schematic diagram of

[0097] Figure 4 is a schematic diagram of coating thickness;

[0098] Reference numerals: 1 - base film; 2 - ceramic layer. DETAILED DESCRIPTION

[0099] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0100] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0101] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.

[0102] raw material:

[0103] PMMA emulsion was purchased from Shenzhen Haodian Technology Co., Ltd., SWA709 brand, pH 6.5, its glass transition temperature was 55, swelling ratio was 70%, and D50 of PMMA particles was 2~5μm;

[0104] The dispersant emulsion was sodium polyacrylate emulsion purchased from Zhuhai Chenyu New Material Technology Co., Ltd., with the brand name CYF-02;

[0105] Binder A emulsion is polyacrylic acid emulsion purchased from Hunan Gaorui Power Material Co., Ltd., brand LIB-S105B;

[0106] Adhesive B emulsion is an acrylic polymer adhesive purchased from ZEON Co., Ltd. of Japan, model BM-900B;

[0107] The wetting agent is a polyether surfactant purchased from Evonik Digo with the brand name KL245.

[0108] Example

[0109] The preparation method of the mixed coating diaphragm is as follows:

[0110] S1. Homogenize the PMMA emulsion (solid content 25%) using a 360° flip rocker;

[0111] S2, dispersing boehmite and dispersant emulsion (solid content 50%) in water to obtain a dispersion; the dispersion time is 20-40 minutes;

[0112] S3, adding the homogenized PMMA emulsion, binder A emulsion (solid content 20%), binder B emulsion (solid content 40%) and wetting agent polyether surfactant (purity 99%) to the dispersion liquid, stirring and dispersing with an anchor stirring paddle to obtain a mixed coating slurry;

[0113] S4. After the slurry is prepared into a finished product, it is continuously stored at 20-150 rpm until it is applied to the coating machine;

[0114] S5. Apply the finished slurry on the base film and dry it to obtain a mixed-coated diaphragm.

[0115] The preparation parameters of each embodiment and comparative example are shown in Table 1.

[0116] Table 1 Preparation parameters of examples and comparative examples

[0117] .

[0118] Observe the mixed coating membrane under a 1K (magnification) electron microscope. Figure 1 The field of view shown in the figure has a rectangular field of view area S0 (the length of the field of view plane is a, the width is b, S0 = a × b), and S0 can be between 5000-20000 μm 2 ;

[0119] In this field of view, the number of fluoropolymer-free particles is N0;

[0120] Randomly select a fluorine-free polymer particle in the field of view (preferably the center area of ​​the field of view, but not limited to this, try to ensure that there are other fluorine-free polymer particles distributed around the selected fluorine-free polymer particle), and place its geometric center point C on the geometric center of one of the regular hexagons. That is, first determine a fluorine-free polymer particle, and use the geometric center point C of this particle as the geometric center of the regular hexagon to draw a regular hexagon with an area of ​​S2=S0 / N0, and divide the field of view according to the size of the regular hexagon to form a regular hexagonal grid structure (N0 regular hexagons, each regular hexagon has an area of ​​S2=S0 / N0);

[0121] The distances between the base point C and the fluorine-free polymer particles in the six regular hexagons adjacent to the regular hexagon where it is located (the six nearest fluorine-free polymer particles) are measured respectively, and are recorded as P1-P6 (i.e., P1, P2, P3, P4, P5, P6), where the maximum value of P1-P6 is recorded as P max , the minimum value of P1-P6 is recorded as P min , according to P max and P min Calculate P: P = (P max +P min ) / 2;

[0122] And calculate the dispersion coefficient α = , and uniformity coefficient ;

[0123] in P x = ,

[0124] P n =1 / 2 P av ,

[0125] P av = .

[0126] The results of various embodiments and comparative examples are shown in Table 2.

[0127] Table 2 Examples and Comparative Examples Results

[0128] .

[0129] Test method:

[0130] [Bond Strength] Place two layers of membrane sample coatings against each other with A4 paper, i.e. A4 paper / membrane / membrane / A4 paper, and pass through a hot press (Qmesys, QM940AS), wherein the temperature of the hot press is set to 100°C and the speed is set to level 1; cut the sample with a width of b = 25 mm (length of 30 cm), peel off 8-10 cm, and clamp it in the upper and lower chucks of a tensile testing machine (Jinan Sike Testing Technology Co., Ltd., TSL-1002) in sequence; start the tensile testing machine to test the peeling force, with a tensile speed of 50 mm / min, test three groups, and take the average value;

[0131] [Bonding strength range] Randomly select 5 values ​​from the 15 test results of the above-mentioned bonding strength test specimens and calculate the range of the 5 values ​​(the difference between the maximum and minimum values);

[0132] [Air permeability] Tested in accordance with the requirements of GB / T36363-2018. Cut 600mm×100mm base film and mixed coating membrane samples, use Wangyan air permeability meter (Asahi Co., Ltd., EG01-55-1MR), test time is 3s, along the 600mm TD direction, measure the air permeability of the base film and mixed coating membrane at any position every 100mm, take the average value of the above 5 test points as the air permeability of the base film and mixed coating membrane; unit coating thickness air permeability value = (mixed coating membrane air permeability - base film air permeability) / coating thickness;

[0133] [Heat shrinkage rate] Tested in accordance with the requirements of GB / T36363-2018. Cut a sample of 10cm×10cm, mark the transverse TD and longitudinal MD on the sample, measure the transverse and longitudinal widths with a fully automatic image measuring projector (Kunshan Gaopin Precision Instrument Co., Ltd., GP-300C), clamp the sample between two sealed A4 papers, place the sample in a 130℃ oven for 1h, and measure the transverse and longitudinal widths with a fully automatic image measuring projector after the sample returns to room temperature. Measure 3 times and take the average value:

[0134] MD heat shrinkage rate (%) = (MD length before heating - MD length after heating) ÷ MD length before heating × 100;

[0135] TD heat shrinkage rate (%) = (TD length before heating - TD length after heating) ÷ TD length before heating × 100;

[0136] [Powder loss rate] The diaphragm was pulled over a roller (diameter 150mm, material: carbon fiber) at a force of 0.04N / mm for 20 times (wrapping angle of 90 degrees), and an electron microscope picture of the diaphragm after the roller was taken using an ultra-depth microscope (under 1K times electron microscope field of view, Keyence, VHX-7000N). The powder loss rate is the number of fluorine-free polymer particles dropped in the field of view / the total number of fluorine-free polymer particles in the field of view. The test was conducted 3 times at random and the average value was taken. The number of fluorine-free polymer particles dropped is the number of pits formed on the surface of the base film by the dropped fluorine-free polymer.

[0137] [Coverage] An ultra-depth-of-field microscope (1K-fold electron microscope field of view, Keyence, VHX-7000N) was used to take electron microscope images of the diaphragm. The coverage area of ​​the fluorine-free polymer particles and the total area of ​​the diaphragm under the field of view were calculated using the microscope. The coverage rate was the coverage area of ​​the fluorine-free polymer particles under the field of view / the total area of ​​the diaphragm under the field of view. Three random samples were taken for testing and the average value was taken.

[0138] The parameter results of each embodiment and comparative example are shown in Table 3.

[0139] Table 3 Parameter results of the embodiments and comparative examples

[0140] .

[0141] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A mixed coating diaphragm with uniformly distributed coating polymer, characterized in that: A base film and a mixed coating covering one or both sides of the base film, wherein the base film comprises a polyolefin microporous film with polyolefin as a main component, the mixed coating comprises fluorine-free polymer particles and inorganic particles, the inorganic particles are continuously distributed in the mixed coating, and the fluorine-free polymer particles are discretely distributed in the inorganic particles; The mixed coating has the following characteristics in the field of view of 1K electron microscope, field of view area S0: (1) The number of fluorine-free polymer particles N0 in the field of view is 7-1000; (2) Taking point C, the geometric center of a fluorine-free polymer particle in the field of view, as the geometric center of a regular hexagon, the field of view is divided into a regular hexagonal grid structure, and the regular hexagonal area of ​​the regular hexagonal grid is S2=S0 / N0; taking point C as the base point, measuring the distance between point C and the geometric centers of the six fluorine-free polymer particles closest to point C, and recording them as P1-P6; Satisfies the following relationship: The dispersion coefficient α is less than 1.5, and Uniformity coefficient β<1.5; Where, α= , , ; P max is the maximum value of P1-P6, P min is the minimum value of P1-P6, P x = , P n =1 / 2 P av , P av = , and P n ≤ P ≤ P x; P n , P x , P av is the theoretical calculated value under ideal state distribution, P n It represents the shortest distance from the geometric center of a regular hexagon to the border (side length) of its adjacent regular hexagon; P x It represents the longest distance from the geometric center of a regular hexagon to the border (side length) of its adjacent regular hexagon; P av Represents the distance between the geometric centers of two adjacent regular hexagons.

2. The mixed coating diaphragm with uniformly distributed coating polymer according to claim 1, characterized in that: The bonding strength of the mixed coating membrane is > 0.8N / m; and / or The maximum difference in the bonding strength of the mixed coating membrane is <0.5N / m; and / or The added value of air permeability per unit coating thickness of mixed coating membrane is <50sec / 100cc / μm.

3. The mixed coating diaphragm with uniform distribution of coating polymer according to claim 1, characterized in that: The heat shrinkage of the co-coated separator in the machine direction MD and transverse direction TD after being kept at 130°C for 1 hour is less than 5%; and / or The powder loss rate of the mixed coating separator is <5%.

4. The mixed coating diaphragm with uniform distribution of coating polymer according to claim 1, characterized in that: The coverage of the non-fluoropolymer particles in the hybrid coating is <39%.

5. The mixed coating diaphragm with uniformly distributed coating polymer according to claim 1, characterized in that: The fluorine-free polymer particles are one or more selected from polymethyl methacrylate, thermoplastic polyurethane elastomer rubber, and polyethylene terephthalate; The average particle size D50 of the fluorine-free polymer particles is 0.5-10 μm.

6. The mixed coating diaphragm with uniform distribution of coating polymer according to claim 1, characterized in that: The inorganic particles are one or more selected from α-alumina, γ-alumina, boehmite, calcium carbonate, barium sulfate, barium titanate, hydrotalcite, montmorillonite, spinel, titanium dioxide, silicon dioxide, zirconium dioxide, magnesium oxide, calcium oxide, beryllium oxide, magnesium hydroxide, calcium hydroxide, and silicon carbide; The average particle size D50 of the inorganic particles is 0.05-1.5 μm.

7. A method for preparing a mixed coating membrane with uniformly distributed coating polymer according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Homogenize the fluorine-free polymer emulsion using a 360° flip rocker; the solid content of the fluorine-free polymer emulsion is 8-45%; the homogenization time is 20-60 minutes; S2, dispersing the inorganic particles and the dispersant emulsion in water to obtain a dispersion; the dispersion time is 20-40 minutes; S3, adding the homogenized fluorine-free polymer emulsion, binder A emulsion, binder B emulsion and wetting agent to the dispersion liquid, stirring and dispersing to obtain a mixed slurry; the stirring and dispersing temperature is 5-40°C, the stirring and dispersing speed is 100-1000rpm, and the stirring and dispersing time is 20-60min; the viscosity of the mixed slurry is 30-300mPa·S, and the solid content of the mixed slurry is 20-40%; S4. After the slurry is prepared into a finished product, it is continuously stored at 20-150 rpm until it is applied to the coating machine; S5. Apply the finished slurry on the base film, first dry it at 50-70° C., then dry it at 70-90° C., and coat it at a speed of 100-200 m / min to obtain a mixed coating separator having a mixed coating layer.

8. The preparation method according to claim 7, characterized in that: The dispersant is one or more selected from sodium polyacrylate, triethylhexyl phosphoric acid, sodium lauryl sulfate, methyl amyl alcohol, polyacrylamide, guar gum, and fatty acid polyethylene glycol ester; Binder A is one or more selected from acrylic acid, acrylic polymer, and polyacrylonitrile; Binder B is one or more selected from polyacrylate, polymethyl cellulose, SBR, and polyvinyl alcohol; The wetting agent is one or more selected from polyoxyethylene alkylphenol ether, polyoxyethylene fatty alcohol ether, and polyoxyethylene polyoxypropylene block copolymer.

9. The preparation method according to claim 7, characterized in that: The mixed coating slurry includes the following components by mass: 0.5-35 parts of fluorine-free polymer emulsion, 15-35 parts of inorganic particles, 0.2-1 parts of dispersant emulsion, 0.5-5 parts of binder A emulsion, 0.5-5 parts of binder B emulsion, 0.001-0.1 parts of wetting agent and 40-60 parts of water.

10. A secondary battery, characterized in that: The invention comprises a mixed coating diaphragm with uniform distribution of coating polymer as described in any one of claims 1 to 6 or a mixed coating diaphragm with uniform distribution of coating polymer prepared by the preparation method as described in any one of claims 7 to 9.

Citation Information

Patent Citations

  • Preparation method of PMMA (polymethyl methacrylate) and PMMA copolymer mixed coating diaphragm

    CN106784531A

  • Al2O3 & PVDF & PMMA mixed coating slurry, composite lithium ion battery diaphragm and lithium ion battery

    CN111987276A

  • Diaphragm with high circulation rate and preparation method thereof

    CN115483500A

  • Organic / inorganic composite porous isolating membrane

    CN101707242A

  • Battery diaphragm, preparation method thereof and battery

    CN116454542A